Political Interaction in the Process of Establishing the Regional Budget of North Sumatera Province - Martuama Saragih; Tjahya Supriatna; Sampara Lukman; Dety Mulyanti (GoAcademica Research & Publishing, 2019)
The purpose of this study was to analyze political interaction in the process of establishing the North Sumatera Province Regional Budget. Research using qualitative research. Research informants 13 people determined by the snowball technique. Secondary data collection uses a literature study; Primary data collection using interview and observation techniques. Data analysis in this study used descriptive analysis and triangulation. Political interaction in the process of establishing the North Sumatera Province APBD is a government communication activity that takes place between executive officials and legislative members in the context of implementing the regional financial management system and become an integral part of government management. Political interactions that occur in the context of establishing regional financial policies for one fiscal year can be either positive or negative. Positive nuance if in the process of political interaction there is a process of interaction of power that is entirely focused on the interests of the community, and it is difficult to find practices of corruption, collusion, and nepotism (KKN). Negative nuances if in the process of political interaction intertwined a process of interaction of power that is not entirely directed at the interests of the community, and indicates the existence of KKN practices. From the phenomenon of corrupt behavior involving the Governor and a number of North Sumatera Provincial legislative members in the past few years, it is clearly indicated that the process of power interaction between executive officials and legislative members could be an opportunity for KKN. That is, given the fact that power tends to be corrupt, the political interaction that takes place in the determination of the regional budget can provide opportunities for corrupt practices that harm the country and cause the people to be stiff. The new model arranged is Positive Negotiated Budget Political Model with the definition: Positive Negotiated Budget Political Model is a government communication pattern that takes place in the formulation, discussion and determination of budget policies that are entirely in the public interest and anti-corruption, collusion and nepotism revealed from the motive negotiation, the proposition of negotiation and the consequences of negotiations are positive. With this definition, three dimensions of budget politics negotiation are included: (1) Dimensions of positive nuanced budget negotiation motives, (2) Dimensions of positive budget negotiation proposition, (3) Dimensions of the consequences of positive budget negotiation.